2020
DOI: 10.1016/j.eats.2019.09.023
|View full text |Cite
|
Sign up to set email alerts
|

Tibial Plateau With Arthroscopic Reduction–Internal Fixation

Abstract: Arthroscopic-assisted internal fixation is an ideal technique for visualizing chondral reduction during tibial open reductioneinternal fixation. Typically, open reductioneinternal fixation is performed using radiographic and Fluoroscan imaging (Hologic, Bedford, MA) for reduction of subchondral bone. However, reduction without visualization does not ensure chondral surface reduction. This Technical Note and supplemental video describe an arthroscopic-assisted technique involving the tibial plateau that gives c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 9 publications
0
7
0
Order By: Relevance
“…Cassard et al found that an arthroscopic approach allowed for more rapid rehabilitation, a decrease in overall hospital length of stay, and a decrease in the rate of complications [14]. Overall, the literature establishes that the arthroscopic-assisted technique has similar and at times better clinical scores compared to the open technique [4,[11][12][13][14][15][16][17][18][19]. When compared to the use of fluoroscopy, in the setting of closed reduction technique, Lobenhoffer et al demonstrated that there was no discernible difference between the two techniques [15].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cassard et al found that an arthroscopic approach allowed for more rapid rehabilitation, a decrease in overall hospital length of stay, and a decrease in the rate of complications [14]. Overall, the literature establishes that the arthroscopic-assisted technique has similar and at times better clinical scores compared to the open technique [4,[11][12][13][14][15][16][17][18][19]. When compared to the use of fluoroscopy, in the setting of closed reduction technique, Lobenhoffer et al demonstrated that there was no discernible difference between the two techniques [15].…”
Section: Discussionmentioning
confidence: 99%
“…When compared to the use of fluoroscopy, in the setting of closed reduction technique, Lobenhoffer et al demonstrated that there was no discernible difference between the two techniques [ 15 ]. However, in another study, Alvarez et al showed that arthroscopy was better than fluoroscopy, providing greater visualization, which in turn allowed for more precise tamping and reduction of the tibial plateau [ 19 ]. Ziogas et al reported in a case report that the use of arthroscopy in balloon osteoplasty showed an excellent clinical outcome at weeks 6, 12, and 24 post-op [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…There were 11 (17.5%) bullets removed in an arthroscopic-assisted fashion with a small arthrotomy incision, while the remainder (82.5%) required no additional incisions. Mechanisms of arthroscopic bullet retrieval included grasper (15), ronguer (3), threaded guidewire (2), and shaver (1). Approximately, one-third of patients (30.6%) were noted to receive IV antibiotics (first-generation cephalosporin), while all other cases did not report the use or disuse of antibiotic prophylaxis.…”
Section: Discussionmentioning
confidence: 99%
“…49,50 A recent study by Alvarez et al discussed arthroscopic reduction and internal fixation of tibial plateau fractures, noting benefits of arthroscopic treatment including clear visualization of articular surface, less intrusiveness, and the opportunity for multiple interventions such as meniscal or cartilage repair at time of the index operation. 15 Botser et al compared open surgical hip dislocation with arthroscopic treatment for femoroacetabular impingement and highlighted lower complication rates, higher rate of return to sport for professional athletes, and greater increase in modified Harris hip score, providing a validated scoring measure, favoring arthroscopic treatment. 49 In the original technique article by Ganz et al regarding surgical dislocation of the hip, complications including heterotopic officiation in 37% of patients and 'saddleback deformity' of subcutaneous fat from closure of the incision were noted.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation